Comparison of the Effectiveness of Oral Progesterone and Micronized Progesterone Pessary in Reducing the Spontaneous Preterm Birth Incidences - Saima Iqbal, Sadia Hanif, Zaib Un Nisa, Ambreen Shabbir, Khizera Anwar, Nighat Afridi (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study is to compare the effectiveness of oral progesterone and micronized progesterone pessary in reducing the spontaneous preterm births incidence. Study Design: Randomized controlled trial Place and Duration: Gynaecology and Obstetrics Department of Combined Military Hospital, Peshawar from January 2021 to December 2021. Methods: Total 112 pregnant females were presented in this study. Included females were aged between 18-45 years. After taking informed written consent, detailed demographics of enrolled cases included age, BMI, parity and gestational age was recorded. Females were divided in two groups. Group I received oral progesterone in 56 females and group II received micronized progesterone pessary. Post-operative outcomes among both groups were assessed. SPSS 23.0 was used to analyze all data. Results: Among 112 cases, 35 (31.3%) had age 18-25 years, 45 (40.2%) females had age 26-35 years and 32 (28.6%) cases had age 36-45 years. 64 (57.1%) patients had BMI <25kg/m2 and 48 (42.9%) cases had BMI >25kg/m2. Mean parity in group I was 2.5±1.23 and in group II parity was 1.72±3.16. Mean gestational age of the patients in group I was 33.16±10.42 weeks and in group II mean gestational age was 34.17±8.23 weeks. Frequency of c-section in both groups were higher as compared to vaginal delivery with p value <0.003. Mean time of prolongation of pregnancy in group I was 18.22±6.33 days and in group II mean time was 30.7±5.47 days. We found that micronized progesterone cyclogest pessary was effective in terms of reducing NICU admissions, maternal systemic complications, preterm C-section, tocolysis use, side effects, intraventricular haemorrhage and perinatal mortality as compared to oral progesterone. Conclusion: Preventive micronized progesterone pessary was found to be more effective than oral progesterone (dydrogesterone) in reducing premature birth among women at high-risk of premature delivery. Keywords: Oral Progesterone, Micronized Progesterone Pessary, Preterm Birth, Side Effects